Comparison of the metabolic activation of environmental carcinogens in mouse embryonic stem cells and mouse embryonic fibroblasts. Issue 1 (February 2015) - Krais, Annette M.; Mühlbauer, Karl-Rudolf; Kucab, Jill E.; Chinbuah, Helena; Cornelius, Michael G.; Wei, Quan-Xiang; Hollstein, Monica; Phillips, David H.; Arlt, Volker M.; Schmeiser, Heinz H.
Highlights ES cells and MEF have the metabolic competence to activate environmental carcinogens. Carcinogen-induced genotoxicity in MEFs is higher than in ES cells. MEFs have higher metabolic capacity than ES cells. Metabolic capacity depends on the carcinogen studied.